Talazumiyah al-Rabth fi al-Kitabah al-Insyaiyyah Baina al-Uslub wa al-Tauzhif wa al-Maharah: Dirasah fi Maharah al-Kitabah li al-Nathiqin bi Ghair al-Arabiyyah - Bin Zabidin, Mohd Azizul Rahman; Awad, Ragab Ibrahim Ahmed; Alawadi, Elsayed Mohamed Salem; Mahdi, Rijal (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This research is studying about one of the most important skills in the Arabic language that is hoped to be acquired by Malaysian students, either in secondary or university level. The aim of teaching essay writing at these two stages is to enable students to express a topic in writing in a good manner and in an organized manner of various kinds according to the correct rules of the Arabic language. It is noticeable that non-Arabic speaking students, especially Malaysian students, despite their mastery of grammatical and morphological rules, still fall into stylistic errors resulting from their lack of understanding of the â€˜ibarÄt al rÄbitah (conjunctive phrases), their connotations and their functions in structural writing. Based on all of the foregoing, this research deals with theories related to the concept of stylistic errors and the concept of style and its elements, especially in the field of teaching Arabic as a second language. The research followed the descriptive and analytical method and was limited to analysing the â€˜ibarÄt al rÄbitah (conjunctive phrases) in the modern Arabic language and analysing their meanings, functions, and uses in structural writing. The research has reached many results, the most important of which is â€˜ibarÄt al rÄbitah (conjunctive phrases) as one of the most important elements of the Arabic language style that is hoped to be provided to Malaysian students, especially in the secondary and university degree stage, to control the stylistically sound structural writing. The research also stated some recommendations to facilitate the teaching and application of â€˜ibarÄt al rÄbitah (conjunctive phrases) at the secondary and university levels.